Proactive asthma care in childhood: general practice based randomised controlled trial. Issue 7416 (18th September 2003) - Glasgow, Nicholas J; Ponsonby, Anne-Louise; Yates, Rachel; Beilby, Justin; Dugdale, Paul
Abstract: Objectives To assess the feasibility and effectiveness of a general practice based, proactive system of asthma care in children. Design Randomised controlled trial with cluster sampling by general practice. Setting General practices in the northern region of the Australian Capital Territory. Participants 174 children with moderate to severe asthma who attended 24 general practitioners. Intervention System of structured asthma care (the 3+ visit plan), with participating families reminded to attend the general practitioner. Main outcome measures Process measures: rates for asthma consultations with general practitioner, written asthma plans, completion of the 3+ visit plan; clinical measures: rates for emergency department visits for asthma, days absent from school, symptom-free days, symptoms over the past year, activity limitation over the past year, and asthma drug use over the past year; spirometric lung function measures before and after cold air challenge. Results Intervention group children had significantly more asthma related consultations (odds ratio for three or more asthma related consultations 3.8 (95% confidence interval 1.9 to 7.6; P = 0.0001), written asthma plans (2.2 (1.2 to 4.1); P = 0.01), and completed 3+ visit plans (24.2 (5.7 to 103.2); P = 0.0001) than control children and a mean reduction in measurements of forced expiratory volume in one second after cold air challenge of 2.6% (1.7 to 3.5); P = 0.0001) less than control children. The number needed to treat (benefit) for one additional written asthma action plan was 5 (3 to 41) children. Intervention group children had lower emergency department attendance rates for asthma (odds ratio 0.4 (0.2 to 1.04); P = 0.06) and less speech limiting wheeze (0.2 (0.1 to 0.4); P = 0.0001) than control children and were more likely to use a spacer (2.8 (1.6 to 4.7); P = 0.0001). No differences occurred in number of days absent from school or symptom-free day scores. Conclusions Proactive care with active recall for children with moderate to severe asthma is feasible in general practice and seems to be beneficial.